The gluN2B subunit of NMDARs and its role in glutamatergic synapses : towards the characterization of the proteome of postsynaptic densities from wild-type and GluN2B-null cultured neurons - Rio, Pedro Daniel Rocha (2011)
Dissertação de mestrado em Biologia Celular e Molecular apresentada ao Departamento Ciências da Vida da Faculdade de Ciências e Tecnologia da Universidade de Coimbra.